Assessing the benefits from joining the International beef cattle genetic evaluation (Interbeef) at SLU’s Interbull Centre - Osorio Gallardo, Tzayhri (2021)
In 2019 the Interbeef Working Group started offering a new Service: the “Interbeef Pilot run”. The Service, developed and provided by Interbull Centre, consists in an international genetic evaluation for beef breeds using pre-defined genetic parameters. In 2020, Estonia expressed interest in Interbeef Pilot run for the evaluation of adjusted weaning weight (aww) in Limousin and Aberdeen-Angus breeds. The aim of this project was to perform the Interbeef Pilot run using performances and pedigree information submitted by Estonia jointly with the international data available for the Interbeef Service. The service was expected to offer Estonia access to a wide international panel of animals whose EBVs were expressed on the local scale, additionally to an increase in EBV reliabilities of animals in Estonia. This would facilitate the selection of the bulls with best EBVs at national and international level. International EBVs and reliabilities were obtained using a multi-trait animal model where aww performances from different organisations are considered as different traits. Across country genetic correlations for Estonia were set as the average of the correlations estimated for the other participating organisations in the Interbeef routine aww evaluation. Pseudo-national EBVs were computed by setting the across country genetic correlations in the model to zero. The pseudo-national and international EBVs and reliabilities were compared assessing the theoretical benefit of joining the international genetic evaluation. As a result from the Pilot run, Estonia received international EBVs on its own scale for all animals included in the international pedigree. An average increase in international EBV reliability of 0.12 and 0.09 was observed for Estonian Limousin and Aberdeen Angus respectively. The main foreign sire countries were DFS (Denmark, Finland, Sweden) for Limousin and the UK in Aberdeen Angus. The number of connecting sires between Estonia and the participating countries in Interbeef was limited, which should be taken into account in case Estonia would join the international evaluations in the future. Based on the Pilot run results, Estonia would benefit from joining the Interbeef evaluation.